Isolated scapular lesion of langerhans cell histiocytosis detected by (18)F-FDG PET/CT - TUROĞLU, HALİL TURGUT; ÖZGÜVEN, SALİH (My University, 2022)
Langerhans cell histiocytosis (LCH) is a rare disease that occurs mainly in pediatric patients and most adult LCH is considered a part of multisystem or multifocal disease. Only 7.3% of cases present as unifocal bone lesion. Herein, we present a case of an isolated scapular lesion of LCH in a 48-year-old man

Langerhans hücreli histiyositoz (LHH), çoğunlukla pediatrik hastalarda ortaya çıkar ve yetişkin LHH genelikle multisistem veya multifokal hastalığın bir parçası olarak görülen nadir bir hastalıktır. Olguların sadece %7,3’ü tek odaklı kemik lezyonu olarak karşımıza çıkmaktadır.
Keywords: Langerhans cell histiocytosis; 18F-FDG PET/CT; bone; Langerhans hücreli histiyositoz; 18F-FDG PET/BT; kemik